PSIKOEDUKASI MENGATASI KECANDUAN GADGET PADA ANAK - Novita Maulidya Jalal; Rahmawati Syam; St.Hadjar Nurul Istiqamah; Muhrajan Piara; Irdianti Irdianti (Yayasan Pendidikan Penelitian Pengabdian Algero, 2022)
Gadget users in general and smartphones in particular are growing rapidly in Indonesia, including children. The purpose of this service is to provide information regarding the impact of gadgets and strategies for using gadgets on children to minimize the impact of excessive gadget use on children. The service method used is to carry out psychoeducation for parents so that parents know how to deal with gadget disturbances in children. The results of the service show that with psychoeducation, parents obtain information related to the characteristics of child development, children's motives for playing gadgets, strategies for using gadgets in children so that children can use gadgets for positive purposes. Thus, it can be concluded that psychoeducation can have an effect on increasing parental knowledge regarding strategies for using gadgets in children. The suggestion for the implementation of further dedication is that parents are involved not only mothers, but fathers are also involved because the effectiveness of gadget management strategies for children requires discipline. for all family members at home.